Annual Update on SDR Trading Operations. (Policy Papers; Policy Paper ;, 2021)
This paper provides an update on the status of the SDR trading market and operations. In over three decades, SDRs have been exchanged for freely usable currencies in transactions by agreement primarily through the Voluntary Trading Arrangements (VTAs). The VTAs are bilateral arrangements between the Fund and SDR participants or prescribed holders, in which the VTA members agree to buy and sell SDRs within certain limits. A fraction of transactions by agreement-sales or acquisitions of SDRs-were arranged directly between parties.